PELATIHAN GURU SD DALAM MENDESAIN PEMBELAJARAN BERMAKNA BERBASIS DEEP LEARNING PADA PADA KURIKULUM MERDEKA GURU UPT PSF SDN SUMANNA MAKASSAR - Muh Aidil Sudarmono R; Abdul Wahab; Dzata Bahjah; Mulyasti Andasari; Syarfina Arfani Guslob (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This community service activity is entitled “Training for Elementary School Teachers in Designing Meaningful Learning Based on Deep Learning in the Merdeka Curriculum at SPF SDN Sumanna Makassar.” The purpose of this program is to enable elementary school teachers to design meaningful learning based on deep learning in the context of the Merdeka Curriculum. The specific objectives of this activity are: (1) to develop a deep understanding among teachers about the concept of deep learning within the Merdeka Curriculum, (2) to enable teachers to design meaningful learning experiences that foster students’ critical, creative, collaborative, and communicative thinking skills, and (3) to produce examples of teaching materials or learning modules that implement the principles of deep learning. The implementation method of this activity consists of two main parts: (1) delivering materials related to the concept of deep learning in the Merdeka Curriculum and meaningful learning design, and (2) providing mentoring and practical sessions to assist teachers in designing teaching materials and learning activities based on deep learning. The community service was carried out through four main stages: planning, implementation, evaluation, and reflection.